Written for us: Paul's interpretation of scripture and the history of midrash - Fisch, Yael (Journal for the study of Judaism / Supplements, 2023)
"This volume re-introduces Paul into the study of midrash. Though Paul writes and interprets scripture in Greek and the Tannaim in Hebrew, and despite grave methodological difficulties in claiming direct and substantial cultural contact between these literary traditions, this book argues that Paul is a crucial source for the study of rabbinic midrash and vice versa. Fisch offers fresh perspectives on reading practices that Paul and the Tannaim uniquely share; on Paul's concept of nomos, and its implications on the reconstructed history of the Tannaitic twofold-Torah, Oral and Written; on the relationship between allegory and midrash as hermeneutical systems; and on competing conceptualizations of ideal readers"--